Uji aktivitas antibakteri ekstrak etanol dan berbagai fraksi daun rimbang (Solanum torvum Swartz) terhadap Bakteri staphylococcus aureus. - Sari, Devi Purnama; Kusumastuti , Melati Yulia; Safriana, Safriana (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Traditional medicine is now seen as an opportunity for modern medicine because it is considered safer and believed to have complementary or synergistic effects, making traditional medicine beneficial. Rimbang leaves (Solanum torvum Swartz) are plants that can be utilized in traditional medicine. This study aims to determine whether ethanol extracts and various fractions of rimbang leaves have antibacterial activity against Staphylococcus aureus bacteria. Phytochemical screening results show that ethanol extract and ethyl acetate fraction of rimbang leaves contain secondary metabolites including alkaloids, flavonoids, saponins, tannins, steroids/triterpenoids, and glycosides. The ethanol fraction consists of alkaloids, flavonoids, saponins, and glycosides, while it does not include steroids/triterpenoids. The n-hexane fraction only contains alkaloids and steroids/triterpenoids. The antibacterial activity against Staphylococcus aureus at a dose of 500 mg/ml shows that ethanol extract has an average inhibition zone of 14.83 mm, ethyl acetate fraction has an average of 21.67 mm, and ethanol fraction has an average inhibition zone diameter of 8.17 mm.